ANALISIS MODEL PENDIDIKAN ISLAM BERBASIS EKOLOGI DI SEKOLAH MENENGAH PERTAMA - Awal Novanto, Riza; Hidayati, Nur Rahmah; Maesarah, El Syifa (JURNAL TARBIYAH, 2025)
This study aims to analyze the implementation of Ecology-Based Islamic Education and its leading indicators at SMP At-Tin UMP Margasari, emphasizing the Islamic concept of human responsibility as a caliph on earth. Using a qualitative case study approach, in-depth interviews were conducted with the principal and students to explore integrating Islamic values into ecological education. Data were analyzed using NVivo software to facilitate coding and grouping of themes, including "Integration of Islamic and Ecological Education," "Ecological Activities in the Curriculum," and "Impact on Student Behavior." The findings indicate that ecological practices implemented in the curriculum increase environmental awareness as part of religious obligations, which impacts students' daily behaviors such as waste management and energy saving. Practical activities such as Green Schools and agricultural projects also strengthen students' understanding of sustainability principles. This study provides practical insights for schools seeking to integrate ecological awareness with religious values, supporting sustainable environmental practices as part of Islamic education. Further studies are recommended to expand the sample size and use longitudinal methods to assess the long-term impact on student behavior.